A Maximum Likelihood Estimation of the Thermal Resistance of a Cavity Wall from On-site Measurements. (November 2015) - Deconinck, An-Heleen; Roels, Staf
Abstract: The thermal resistances of a building's components are main parameters in assessing the overall thermal performance of the building envelope. In order to assess the actual, as-built thermal performance of building components, a reliable thermal characterization of building elements from on-site measurements is required. In this paper, the thermal resistance of a cavity wall is estimated by means of maximum likelihood estimation (MLE) from on-site meas rements. To evaluate the performance of MLE the method is applied on various data sets of the outdoor test wall. Based on the results for all data sets, the potentials of the dynamic estimation technique are considered. Special attention is paid to the accuracy of the estimation results in function of the measurement length and the measurement period throughout theyear.